NADPH–Cytochrome P450 Reductase Mediates the Resistance of Aphis (Toxoptera) citricidus (Kirkaldy) to Abamectin - Jing, Tian-Xing; Tan, Yang; Ding, Bi-Yue; Dou, Wei; Wei, Dan-Dan; Wang, Jin-Jun (Frontiers in Physiology, 2018)
NADPH-cytochrome P450 reductase (CPR) plays an essential role in the cytochrome P450 enzyme system, which aids in the metabolism of endogenous and exogenous compounds including the detoxification of insecticides. In this study, the CPR transcript in Aphis (Toxoptera) citricidus (Kirkaldy) was cloned, and the deduced amino acid sequence contained an N-terminal membrane anchor, three conserved binding domains (flavin mononucleotide, flavin adeninedinucleotide, and nicotinamide adenine dinucleotide phosphate), a flavin adeninedinucleotide-binding motif, and catalytic residues. Based on phylogenetic analysis, AcCPR was grouped in the hemipteran branch. AcCPR was ubiquitously expressed at all developmental stages and was most abundant in the adults and least abundant in third instar nymphs. Compared with other tested tissues of adults, the expression level of AcCPR was significantly high in the gut. Feeding double-stranded RNA of AcCPR reduced the AcCPR mRNA level and the activity of AcCPR in aphids, and the treated insects exhibited higher susceptibility to abamectin than the control group. Furthermore, the heterologous overexpression of AcCPR in Sf9 cells resulted in a greater viability than control cells when treated with abamectin. All results demonstrated that AcCPR may contribute to the resistance of A.citricidus to abamectin, and CPR may be a potential target for novel insecticide design or a new factor in the development of insecticide resistance.